An analysis of public primary school teachers’ dealing with difference in the absence of a multicultural education policy in Turkey - Esen, Hüseyin. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study aims to analyze primary school teachers’ dealing with difference in the absence of a multicultural education policy in public primary schools in Turkey. The study explores four basic issues: i) primary school teachers’ attitudes towards difference, ii) how primary school teachers deal with difference in the absence of a multicultural education policy, iii) teachers’ assessment of the current curriculum and school culture with regard to difference, and iv) teachers’ perceptions of their own competence level with regards to dealing with difference. Within the scope of this study, qualitative methods of inquiry, particularly interview study method was employed. The researcher developed a semi-structured interview form and 15 primary school teachers were interviewed. After the interviews were fully transcribed, the gathered data was content analyzed. The research demonstrates that teachers have differing views of the society. Some see it as a uniform whole; others perceive it as a fragmented structure, while some of the teachers see it as a colorful mosaic. It is also clear from the research findings that teachers have different attitudes towards diversity. Some of them say that they are indifferent to difference; some of them have a reductionist view of diversity and they also focus on individual level differences while others have tolerance towards diversity. Some of the teachers think that curriculum renders diversity invisible while others claim that that the new curriculum since 2005 is attentive to diversity and more inclusive than it used to be. It is also very striking that 11 out of 15 teachers think that teachers have biases towards diversity while none of the teachers find themselves biased. The research findings demonstrate that teachers have not received any in-service or pre-service education to deal with diversity. Those elder teachers feel themselves much more experienced in dealing with diversity. 13 out of 15 teachers state their need for further education in dealing with diversity. According to the findings of the research, although never received any training in dealing with diversity issues, it was observed that teachers have developed their own ways of dealing with diversity and diversity related problems.
Keywords: Multicultural education -- Turkey.; Primary school teachers -- Turkey.